WAYS OF IMPROVEMENT OF THE INFORMATIVE PROVIDING OF LABOUR PROTECTION AT HIGH SCHOOL - Стеліга, І. І.; Семчук, Я. М.; Рошак, Й. І.; Лялюк-Вітер, Г. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The solution of one of the state problems – the creation of the working environment – is connected inse inseparably with the improvement of information supply of labor. World experience shows that it is information on health and safety, presented in proper form allows you to achieve significant results in the provision of safe working conditions sector. The article describes the main trends of information supply improvement of labour protection. Some ways of their solutions are given.